Introducing the Longitudinal Study of Australian Children - LSAC Discussion Paper No.1 - Nicholson, J; Ungerer, J; Wilson, K; Zubrick, S; Sanson, A (My University, 2002)
The Longitudinal Study of Australian Children (LSAC) aims to provide the database for a comprehensive understanding of Australian children's development in the current social, economic and cultural environment, and to become a major element of the evidence base for policy and practice regarding children and their families. This discussion paper focuses on the research questions that LSAC is designed to address and how they will be addressed. It presents an overview of the study, incorporating descriptions of the rationale for the study, relevance for policy development, the conceptual framework, broad and specific research questions, and study design. The paper provides a discussion of current thinking about how the research questions will be addressed, and what data are to be collected.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology